Professional competence of teachers in improving the quality of learning - Syoviana, Elvi; Giantara, Haris; Ramadhan, Fadillah; Month, Thoifatul Lathifah; Syai’un, Ahmad; Fajrina, Helna Putri; Fitri, Hidayatul; Arianti, Nesa; Sarifah, Adia; Ardina, Neta; Abdullah, April Rahmat; Saputra, Riko; Gunawan, Gunawan (Indonesian Research Journal in Education |IRJE|, 2025)
This study sought to examine the implementation of teachers’ professional competence in classroom practices and its impact on the quality of education. The research employed qualitative and quantitative approaches. The subjects comprised eight teachers, three senior Islamic instructors, and 25 students at the Islamic junior high school [MTs] level. Data were collected through interviews, classroom observations, and student questionnaires. The results revealed three key findings. First, there was a strong synergy between professional skills and Islamic principles, with teachers mastering content and pedagogy and embedding adab (ethics) and akhlaq (morals) in their teaching. Second, institutional strategies such as regular training, performance evaluation, and academic culture development effectively enhanced teacher professionalism. Third, teachers’ professional competence significantly affected the quality of education, as reflected in improved student understanding, motivation, and engagement. It was concluded that improving the quality of education at MTs Pesantren Ulul Albab was strongly influenced by teachers' professional competence, supported by Islamic values and well-structured institutional systems.